Synthesis and Characterization of VPI-5 Molecular Sieve from Non-aqueous Systems - Venkatathri, N. (Asian Journal of Chemistry, 2010)
The extra large pore aluminophosphate molecular sieve, VPI-5 has been synthesized from non-aqueous media using hexamethyleneimine template for the first time. Aqueous media VPI-5 samples have been prepared for comparison. X-ray diffraction pattern shows that the synthesized material is similar to reported VPI-5. SEM photograph shows that the morphology is even. TG/DTA and carbon and nitrogen analysis shows that there is 37.12% weight loss due to the loss of the template and water molecules. However, the VPI-5 samples synthesized from aqueous media contain no template. FT-IR spectrum of the sample in framework region is similar to the reported pattern. MAS NMR shows that the sample contains three different aluminium and phosphorus sites.